Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

DEM Investigation of Cyclic Lateral Loading of Granular Backfill for Integral Abutments: Earth Pressure Ratcheting and Settlement Mechanisms - Hao-Biao Chen; Nian-Wu Liu; Hong Wang; Ming-Guang Li; Guang-Zai Chen (Computers and Geotechnics, 2026)

Microenvironment modulation of single-atom Rh sites via fluorinated phosphine polymer skeleton engineering toward boosted hydroformylation performance - Li Huang; Miaojiang Wu; Peng Sun; Mengnan Nie; Yulong Lai; Guang Gao; Zhiwei Huang; Fuwei Li (Chemical Engineering Journal, 2026)

Elucidating interfacial electronic bridge modulation via p–p orbital hybridization in dual-piezoelectric heterojunction for piezo-photocatalytic water decontamination - Meng Dai; Jingcai Chang; Yulin Huang; Hanxuan Li; Xiaoge Wu; Dong Zhai; Shu-guang Wang; Zuoli He (Chemical Engineering Journal, 2026)

Insights into the alleviating effects of exogenous α-ketoglutaric acid on free nitrous acid stress in Tribonema minus and ammonium removal in wastewater - Xinjuan Hu; Mingrui Wu; Teng Li; Xianhui Xue; Xu Yan; Baolong Wang; Lili Chen; Xiangru Xu; Lijuan Meng; Zhen Yu; Mostafa El-Sheekh; Guang Yang; et al. (Bioresource Technology, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

Stochastic analysis of horizontal dynamic response of offshore pipe piles considering hydrodynamic pressure - Bo Yu; Libo Chen; Guang Han; Lichen Li; M. Hesham El Naggar; Wenbing Wu (Ocean Engineering, 2026)

How plant diversity and nitrogen deposition affect the net nutrient retention on temperate extensive green roofs: A case study - Guang Hao; Yihan Wang; Hechen Li; Shaobo Gao; Runze Wu; Zhuolin Li; Jiale Han; Hongyuan Li; Rui Hua; Nan Yang (Ecological Engineering, 2026)

CO2 sequestration via mixed hydrate formation in depleted Class I, II, and III hydrate reservoirs: A comparative study from laboratory to field scale - Hongyu Ye; Ling-ban Wang; Jie Li; Daoyi Chen; Xuezhen Wu; Dayong Li; Guang-jin Chen; Chang-yu Sun; Mucong Zi (Chemical Engineering Journal, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

Improved methods for precise orbit determination of LEO satellites under geomagnetic storm conditions - Tianyu Fan; Ran Li; Ying Xu; Haitao Wu; Guang Yang; Wen Li (GPS Solutions, 2026)

Oxygen vacancy-amplified photoelectrochemical sensing of 8-oxo-guanine DNA glycosylase using Bi6S2O15 nanowires - Chunxia Wu; Yaoxuan Jin; Yuanyuan Sun; Guang-Li Wang (Analytica Chimica Acta, 2026)

Cumulative deformation characteristics of offshore wind turbine structure under long-term marine loading - Zhang Bing-jie; Zhang Xiao-ling; Zhou Guang-li; Wu Yang (Soil Dynamics and Earthquake Engineering, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Comparison of food allergic immune responses in sensitized female and male Balb/c mouse induced by Lateolabrax japonicus tropomyosin - Meng-Si Li; Qing-Mei Liu; Fei Xia; Li-Qiang Zhong; Zhi-Qiang Chen; Ya-Ping Wu; Yu-Ni Liao; Gui-Xia Chen; Yi-Xiang Liu; Guang-Ming Liu (Food and Chemical Toxicology, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Photochemically corrected machine learning framework for real-time VOCs source apportionment in support of air quality management - Yu Han; Xing Peng; Yi Hong; Jiang-Yao Tan; Jiang Wu; Li He; Xiao-Feng Huang; Guang-He Yu; Ke Du (Atmospheric Environment, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

TLR4 knockout ameliorates acute LPS-sensitized tolvaptan-induced idiosyncratic liver injury by disrupting drug metabolism, inflammation, and bile acid homeostasis - Xin Jiang; Yi-xin Hu; Bing-yu Cheng; Jing-wen Hu; Yu-qing Zhao; San-lan Wu; Heng Li; Li-Meng Gong; Guang Feng; Dan Li; Lu-qin Si; Jian-geng Huang (Food and Chemical Toxicology, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Transcriptomic analysis reveals organ-specific adaptations in the gut-liver axis during diet domestication of mandarin fish (Siniperca chuatsi) - Hao-Yu Li; Zhi-Guang Hou; Yi-Huan Xu; Cheng-Bin Wu; Zun-Li Qi; Xiao-Wei Gao; Chun‑Long Zhao; Xin Zhao; Li-Han Zhang (Aquaculture International, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

Plant and microbial pathways driving soil carbon sequestration in dryland leguminous shrublands - Zi-Qiang Yuan; Chao Fang; Xin Song; Yi Wu; Feng Zhang; Xiang-Wen Fang; Guang-Qian Yao; Kevin Van Sundert; Feng-Min Li (Soil and Tillage Research, 2026)

Synergistic inversion of maize leaf chlorophyll using multi-source remote sensing data - Shaoping Sun; Jixuan Yan; Guang Li; Zichen Guo; Wenning Wang; Qiang Li; Kejing Cheng; Xuchun Li; Jiaqin Yuan; Changbo Wu (Irrigation Science, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Analytical solution for the vertical vibration of an end-bearing pipe pile group with defective piles in stratified soil - Chuanhai Zhan; Bo Wang; Guang Han; Hao Liu; Bo Li; Xin Liu; Yunpeng Zhang; Wenbing Wu (Ocean Engineering, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Warming-enhanced soil methane uptake is suppressed by nitrogen deposition in a saline-alkali grassland - Jiangqi Wu; Guang Li; Jing Pen; Jiaying He; Haiyan Wang (Journal of Environmental Management, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Mechanisms by which different structures and compositions of exogenous proteins modulate the physicochemical properties of rice starch gels and the textural characteristics of rice noodles - Chenchen Wu; Chunyan Jia; Ming Wu; Zhuohang Li; Guang Zhang; Xiaofei Liu; Na Zhang (Food Hydrocolloids, 2026)

Critical windows and joint effects of prenatal heat and relative humidity exposure on stillbirth: A prospective longitudinal cohort study - Zhan Li; Yuxin Bi; Shuangying Li; Shaofei Su; Lebing Wang; Juan Li; Shuanghua Xie; Enjie Zhang; Minhui Hu; Shaowen Wu; Jianhui Liu; Chenghong Yin; et al. (Environmental Research, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Perfluorooctane sulfonate (PFOS) induces Caspase-8-mediated pyroptosis via GSDMD and GSDME to drive retinal disease: Evidence from epidemiological and experimental studies - Lu-Yin Wu; Li-Xia Liang; Jia-Xin Zhou; Yun-Ting Zhang; Zeeshan Mohammed; Muhammad Amjad; Yang Zhou; Zhi Wang; Guang-Hui Dong; Wen-Wen Bao (Environmental Pollution, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Model-based insights into temperature-driven declines in groundwater recharge under global warming in Michigan’s Lower Peninsula - Jing Zhang; Si-Chen Wu; Shu-Guang Li; Hua-Sheng Liao; Shi-Tao Peng; Jian-Min Zhang (Hydrological Sciences Journal, 2026)

The catalytic subunit of cAMP-dependent protein kinase in Taenia solium cysticerci (TsPKA-c): A promising molecular target for the development of novel anti-cysticercosis therapeutics - Li-Qun Wang; Guang-Xue Liu; Pan-Hong Liang; Li Li; Tao-Shan Li; Ai-Ming Guo; Tharheer Oluwashola Amuda; Ke-Ke Wu; Yi-Xuan Wu; Hong Yin; Hong-Bin Yan; Xue-Nong Luo (Veterinary Parasitology, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Corrigendum to “Ultrafast improvement of cellulose accessibility via non-dissolving pretreatment with LiBr·3H2O under room temperature” [Carbohydrate Polymers 284 (2022) 119180] - Zhonglei Huang; Guang Yu; Chao Liu; Meiyan Wu; Yanjun Tang; Bin Li; Hui Peng (Carbohydrate Polymers, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Evaluating adverse events of antibacterials in infants: insights from FDA adverse event reporting system (FAERS) data - Kai Yan; Guang Yang; Lixuan Yan; Li Wu; Yang Wang; Peifeng He; Qi Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A 430 Ma hydrothermal origin for magnetite at Bayan Obo - Lan Yang; Yang Li; Yan Yu; Li-Guang Wu; Fang-Yue Wang; Xian-Hua Li (Mineralium Deposita, 2026)

P- and S-Wave Poynting Vectors Derived from the Divergence and Curl Mode Separation for Elastic Wave Reverse Time Migration - Nan Hu; Min-gui Cai; Yang-guang Yin; Yun-sheng Zhao; Hao Li; Jun-wu Li; Bing-feng Zhou (Applied Geophysics, 2026)

Multi-element Distribution Profile in Rats: Effects of Inhalable Intratracheal Instillation of Cr(VI) - Liu Yang; Ningning Li; Wenhui Zhou; Xiaoying Li; Hui Wu; Xiuzhi Zhang; Guang Jia; Shanfa Yu (Biological Trace Element Research, 2026)

High efficiency capture of COD and phosphate in real domestic wastewater by Fe(VI)/PAC combined with high-rate contact stabilization process: Performance and mechanism - Lian Wu; Hang Li; Jinan Zhu; Guang Yang; Yulei Liu; Jun Ma; Lu Wang (Water Research, 2026)

A tripartite pollen killer–protector system confers temperature-sensitive inter-subspecific reproductive isolation in rice - Gousi Li; Yaling Zhang; Haixin Yu; Yongyao Xie; Hao Luo; Yuzhu Wang; Jintao Tang; Jia Zhang; Xianrong Xie; Wubei Zong; Kehong Liu; Xinhe Wang; et al. (Molecular Plant, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

PE microplastics altered microbial resource limitation and C/N use efficiency in cotton rhizosphere soil - Yudong Chen; Xiaotong Li; Yulin Shu; Zhoukang Li; Guang Yang; Jinlong Wang; Qiong Wu; Wen Cao; Eryang Li; Yuehan Liu; Wusong Li; Guanghui Lv (Journal of Hazardous Materials, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

Association between Lipid Accumulation Product and 3-Month Functional Outcome after Ischemic Stroke: the Obesity-Stroke Paradox - Yuan Ren; Ying Zhou; Tian-yu Gu; Yang Cheng; Wei-hua Wu; Xiao-guang Dong; Feng-e Li; Yu-sheng Zhang (Translational Stroke Research, 2026)

Amelioration of manganese-induced oxidative stress and pathological damage in the intestine of Micropterus salmoides by fermented Chinese herbal - Zhiwen Yang; Qiuhong Wu; Guang Fan; Pan Zhou; Songsong Bao; Jin Li; Xiaofei Yang; Xinyue Liu; Fangzhou Jing; Li Jiang (Fish Physiology and Biochemistry, 2026)

Design of BDS-3 signal distortion bias model and analysis of its performance - Saisai Gao; Ran Li; Jiatong Wu; Xiaoyun Wan; Rui Guo; Xiaojie Li; Shanshi Zhou; Guang Yang (Advances in Space Research, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Research on Feature Segmentation Methods for UAV Remote Sensing Images Aimed at Roughness Extraction in Wind Farms - Li-fei Li; Guang-sheng Guo; yuan Song; Jia-yuan Du; Fei Zheng; Zhao-zhong Wu; Xiao-xia Gao (Applied Geophysics, 2026)

Synergetic activation of both peroxydisulfate and bisulfite by Fe³⁺ for efficient singlet oxygen generation and organic pollutant degradation - Xin Zhang; Kangning Huangfu; Xiafei Meng; Jinghua Li; Junpei Ye; Yingxuan Deng; Zhihua Chen; Dapeng Wu; Kai Jiang; Guang-En Yuan; Fenglin Yang (Process Safety and Environmental Protection, 2026)

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

FOXP2-Dependent Vulnerability of RGCs Under Acute Ocular Hypertension - Meifang Yan; Junjian Li; Zihao Zhang; Jieni Wang; Qi Tang; Jialu Wu; Huateng Cao; Xue Li; Jie-Guang Chen (Molecular Neurobiology, 2026)

Astrochronology of the terrestrial mid-Cretaceous Quantou and Denglouku formations in the SK-3 borehole from the Songliao Basin, Northeastern China - Shan Li; Huaichun Wu; Qiang Fang; Runjian Chu; Meinan Shi; Guang Yang; Yuan Gao; Xiaojuan Ma; Youfeng Gao; Chengshan Wang (Cretaceous Research, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Multi-dimensional engineering enables high-yield secretion of β-galactosidase Bgal1–3 in Komagataella phaffii - Guang Li; Xiangpeng Yang; Lei Huang; Jiaying Wang; Xiangrui Wu; Benhong Xu; Liang Li; Hongbin Yuan; Yuhuan Liu; Jinwen Wang; Lichuang Cao (Chemical Engineering Journal, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

The ameliorative effects of fermented Chinese herbal medicine on growth inhibition and liver damage induced by manganese exposure in largemouth bass (Micropterus salmoides) - Pan Zhou; Qiuhong Wu; Guang Fan; Zhiwen Yang; Songsong Bao; Jin Li; Xiaofei Yang; Xinyue Liu; Fangzhou Jing; Li Jiang (Fish Physiology and Biochemistry, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Zircon records carbonatite fractional crystallization and hydrothermal metasomatism during REE mineralization - Yan Yu; Yang Li; Lan Yang; Li-Guang Wu; Xian-Hua Li (Geochimica et Cosmochimica Acta, 2025)

Hydroxycitric acid in functional foods: A multitargeted approach to preventing calcium oxalate nephrolithiasis - Xu-dong Li; Zi-ye Huang; Guang Wang; Yu-yun Wu; Pei Li; Bo-wei Yang; Xing Yang; Jiong-ming Li (Food Bioscience, 2025)

T7 peptide-modified tanshinone IIA-pretreated exosomes promote blood-spinal cord barrier repair after spinal cord injury - Jie Liu; Ziyan Guo; Chenlin Lu; Peiran Chan; Qian Zhu; Runsen Lu; Ziyan Zhu; Mingming Zheng; Juan Wang; Wu Xiong; Guang Kong; Haijun Li (Chemical Engineering Journal, 2025)

CO2 hydrate growth behavior and gas storage capacity in water-absorbing porous media - Le Zhao; Xiao-Hui Wang; Yi-Wei Wu; Zhen-Bin Xu; Li-Yong Bao; Peng Xiao; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Positively correlated singlet and triplet hybridization governed by excited-state energy alignment in organic photovoltaics - Yue Ren; Li-Yuan Peng; Hou Tong; Ming-Yang Li; Xue Wu; Guang-Yan Sun (Chemical Engineering Journal, 2025)

Rock damage and stress evolution of large open-hole straight-hole cutting blasting under different in situ stresses - Yi-ming Sheng; Sheng Zhu; Guang-jin Liu; Li Wu; Yao Cheng (Arabian Journal of Geosciences, 2025)

Optimization of borehole layout in equal-diameter empty hole parallel cut blasting - Yi-ming Sheng; Li Wu; Guang-jin Liu; Yao Cheng (Arabian Journal of Geosciences, 2025)

Comparative transcriptomic analysis of gill tissues in largemouth bass (Micropterus salmoides) under low-temperature stress - Zhi-Guang Hou; Meng-Chao Xing; Li-Han Zhang; Yi-Huan Xu; Xin Zhao; Xiao-Wei Gao; Chun-Long Zhao; Cheng-Bin Wu (Aquaculture International, 2025)

Potential bias of nitrogen deposition effects on nitrous oxide emissions from saline-alkaline grasslands - Guorong Xu; Shuaijun Wang; Shuainan Liu; Jianyu Yuan; Jiangqi Wu; Weiwei Ma; Guang Li (Plant and Soil, 2025)

Tuning plant defenses in a changing world - Jia-Yi Wu; Guang-Can Zhou; Zhen Li; Jia-Yu Xue (Trends in Plant Science, 2025)

Chiral switching of many-body steady states in a dissipative Rydberg gas - Chongwu Xie; Konghao Sun; Kang-Da Wu; Chuan-Feng Li; Guang-Can Guo; Wei Yi; Guo-Yong Xiang (Science Bulletin, 2025)

Oxidative polymerization of PEDOT in YMOF-NH2 framework for electrochemically controlled phosphate removal and enrichment - Zhuangzhuang Bi; Zhangjie Huang; Guang Li; Yuanyuan Guo; Qing Qu; Bo Wu (Journal of Environmental Chemical Engineering, 2025)

Unveiling Moxibustion's Impact on AD Mice Learning and Memory: Role of Mitochondrial Respiratory Chain Complex I Subunit in the Hippocampus - Yuan Shen; Hong-Ying Li; Qing-Qing Yang; Ke Zhang; Shu-Qing Liu; Ning Zhang; Chen-Yu Li; Shu-Guang Yu; Lu-Shuang Xie; Qiao-Feng Wu (Molecular Neurobiology, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Kinase domain diversification drives specificity in BRI1 and non-BRI1 RLKs in brassinosteroid signaling - Khawar Ali; Wenjuan Li; Guang Wu (Plant Science, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance” [Chem. Eng. J. 500 (2024) 156765] - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2025)

Evolution of sexual dimorphism in nonhuman primates - Yuan-Ting Guo; Yijun Yang; Bolun Zhang; Hao Wu; Lei Wang; Baoguo Li; Christopher Opie; Xiao-Guang Qi (Science China Life Sciences, 2025)

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

The impact of dietary fat and fatty acid consumption on human health: A comprehensive review of meta-analyses and the Global Burden of Disease study 2021 - Jianglei Ma; Dingtao Hu; Duocai Li; Yuan Chen; Qingyang Chen; Zhiguo Fan; Guang Wang; Weidong Xu; Guanghui Zhu; Zhixiang Xin; Wanli Cao; Zongqin Zhang; et al. (Trends in Food Science & Technology, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Human-model interaction-based decision support system for optimizing food safety assessment - Canghong Jin; Yuanhong Xiao; Hao Wu; Xiaofeng Ji; Guang Li; Jiangbing Shuai; Pinfeng Yang; Lina Xiong (Food Research International, 2025)

Deficiency of synaptotagmin-1 aggravates pressure overload-induced cardiac hypertrophy and dysfunction via the p38 MAPK signaling pathway in mice - Jing Shen; Junqiu Miao; Lifei Wu; Deping Wang; Guang Li; Haixiong Wang; Jimin Cao (Human Cell, 2025)
Cardiac hypertrophy is a major risk factor for heart failure and sudden cardiac death, but its molecular mechanisms have not been well clarified. Synaptotagmin-1 (SYT1) is an important regulator of exocytosis and apoptosis and has been found expressed in the myocardium, while its functions in heart diseases have rarely been studied. Here, we investigated the role and mechanism of SYT1 in pressure overload-induced cardiac hypertrophy. Transverse aortic constriction (TAC) surgeries were performed to induce cardiac hypertrophy in global Syt1 knockout ( Syt1 +/− ) mice and C57BL/6J wild-type (WT) littermates in vivo, with respective sham mice as negative controls. Cardiomyocyte hypertrophy was induced by angiotensin II (Ang II) in H9C2 cells in vitro. The results showed that SYT1 expression was significantly upregulated in WT-TAC mice and in Ang II-treated H9C2 cells. Blocking angiotensin receptor by losartan decreased SYT1 expression in Ang II-treated H9C2 cells. Syt1 +/− mice showed significantly exacerbated cardiac hypertrophy, dysfunction, fibrosis, apoptosis and phosphorylation of myocardial p38 MAPK in response to TAC compared to WT mice. Knocking down SYT1 using siRNA in H9C2 cells aggravated Ang II-induced cell hypertrophy and apoptosis, and also enhanced p38 MAPK phosphorylation. Inhibition of p38 MAPK by SB203580 significantly alleviated the hypertrophy and apoptosis in Ang II-treated H9C2 cells. We conclude that deficiency of SYT1 aggravates pressure overload-induced cardiac hypertrophy via the p38 MAPK signaling pathway. The study elucidates a novel role of SYT1 in cardiac remodeling.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

SuperDecode: An integrated toolkit for analyzing mutations induced by genome editing - Fuquan Li; Xiyu Tan; Shengting Li; Shaotong Chen; Lin Liu; Jingjing Huang; Gufeng Li; Zijun Lu; Jinwen Wu; Dongchang Zeng; Yanqiu Luo; Xiaoou Dong; et al. (Molecular Plant, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Preparation and evaluation of ozone micro-nano bubbles ice for Litchi precooling - Hao Deng; Li Guo; Guang Wu; Zhe Chen; Farhat Abbas; Qingchun Yin (Food Chemistry, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Improving yield-related traits by editing the promoter and distal regulatory region of heading date genes Ghd7 and PRR37 in elite rice variety Mei Xiang Zhan 2 - Xiaotong Guo; Kangli Sun; Zeqiang Wu; Dongdong Xiao; Yingang Song; Shengting Li; Guangliang Wei; Weitao Li; Yu Hao; Bingqun Xu; Kai Zhang; Nan Liao; et al. (Theoretical and Applied Genetics, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Circular RNA circ_0061183 regulates microglial polarization induced by airborne ultrafine particles in HMC3 cells via sponging miR-98-5p - Hui-Xian Zeng; Shuang-Jian Qin; Qi-Zhen Wu; Qing-Guo Zeng; Jia-Hui Li; Anna Oudin; Katja M. Kanninen; Mo Yang; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Improving the understanding of rainfall-runoff processes: Temporal dynamic of event runoff response in Loess Plateau, China - Qiang Wu; Tianning Xie; Chengshuai Liu; Wenzhong Li; Li Zhang; Guang Ran; Yuanhao Xu; Yehai Tang; Zhenyue Han; Caihong Hu (Journal of Environmental Management, 2025)

Supporting IrO on stable La, Nb-TiO2 with enhanced electron transport for efficient acidic water oxidation - Biao Ran; Yun Wu; Kaiyang Zhang; Rui Yao; Jinping Li; Guang Liu (Fuel, 2025)

Optimized carbonylation treatment of Litopenaeus vannamei matrix decreased its immunoreactivity and improved edible quality, simultaneously - Meng Liu; Ming-Xuan Wu; Fei-Fei Gong; Zhao-Min Sun; Ying Li; Fei Huan; Gui-Xia Chen; Qing-Mei Liu; Hong Liu; Guang-Ming Liu (Food Chemistry, 2025)

Structure-rheological relationship of capillary protein oleogels: The role of particle wettability - Gao-Shang Wang; Long-Yuan Zhang; Guang-Xin Feng; Chuan-Wu Han; Li-Juan Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2025)

Single-cell transcriptome sequencing analysis of physiological and immune profiling of crucian carp (Carassius auratus) gills - Zhi-Guang Hou; Meng-Chao Xing; Jia-Xing Luo; Yi-Huan Xu; Li-Han Zhang; Xiao-Wei Gao; Jiang-Jiang Wang; Fazhan Hanafiah; Waiho Khor; Xin Hao; Xin Zhao; Cheng-Bin Wu (Fish & Shellfish Immunology, 2025)

The emerging roles of particulate matter-changed non-coding RNAs in the pathogenesis of Alzheimer's disease: A comprehensive in silico analysis and review - Hui-Xian Zeng; Shuang-Jian Qin; John Andersson; Shen-Pan Li; Qing-Guo Zeng; Jia-Hui Li; Qi-Zhen Wu; Wen-Jie Meng; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Guang-Hui Dong; et al. (Environmental Pollution, 2025)

Protein-based supramolecular adhesive capable of on-demand adhesion and anti-adhesion for preventing undesired epidural tissue adhesion - Tong Li; Guang Wen; He Zhao; Yang Qu; Han Wu; Yingchuan Sun; Jianwu Zhao; Wen Li (Chemical Engineering Journal, 2025)

Enhanced glucose utilization and succinic acid production in Corynebacterium glutamicum by integration of metabolic engineering and electro-fermentation - Yu-Chen Liang; Kai Li; Xin-Qing Zhao; Feng-Wu Bai; Chen-Guang Liu (Chemical Engineering Journal, 2025)

Precipitation regulates soil organic carbon affected by shrub encroachment along the altitude gradient - Li Liu; Guang Zhao; Daijun Yao; Ning Zong; Yunlong He; Wenchao Wu; Qianxin Jiang; Yangjian Zhang (CATENA, 2025)

Recycling of subducted continent slab in an accretionary orogen: Insight from the Liangwan potassic granitoids in the Tongbai orogen, Central China - Wen-Xiang Zhang; Xing Zhang; Guang-Yan Zhou; Long Li; Huan Chang; Yuan-Bao Wu (Lithos, 2025)

Vegetation degradation and its progressive impact on soil nitrogen mineralization in the Qinghai-Tibet Plateau's alpine wetlands: Insights from a three-year study - Jianan Du; Weiwei Ma; Guang Li; Jianghua Wu; Wenhua Chang (Journal of Environmental Management, 2025)

How to evaluate the reduction effect of the park on PM2.5? Exploratory application of the maximum and cumulative perspective - Pengcheng Li; Yun Chen; Haifeng Niu; Lu Zhang; Yu Tang; Guang Zhu; Zhongyuan Zhang; Yizhe Ma; Wen Wu (Sustainable Cities and Society, 2024)

Potential impact of organophosphate esters on thyroid eye disease based on machine learning and molecular docking - Tianqi Jia; Wenbin Liu; Arturo A. Keller; Lirong Gao; Xiaotian Xu; Wenqi Wu; Xiaoxia Wang; Yang Yu; Guang Zhao; Baohui Li; Jinglin Deng; Tianao Mao; et al. (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

A LiDAR-driven three-dimensional simulation model for far-red solar-induced chlorophyll fluorescence in forests - Shichao Jin; Chunhui Zhan; Weiwei Liu; Lixia Ma; Zhaohui Li; Xiaokang Zhang; Yunfei Wu; Qian Zhang; Guang Zheng; Yongguang Zhang (Remote Sensing of Environment, 2024)

Per- and poly-fluoroalkyl substances (PFAS) accelerate biological aging mediated by increased C-reactive protein - Zongxi Zhao; Jiayan Zhou; Anye Shi; Jingyi Wang; Hongzheng Li; Xiangjun Yin; Jialiang Gao; Ying Wu; Jinlin Li; Ya Xuan Sun; Hao Yan; Yige Li; et al. (Journal of Hazardous Materials, 2024)

Nitrogen-rich and core-sheath polyamide/polyethyleneimine@Zr-MOF for iodine adsorption and nerve agent simulant degradation - Yu-Xuan Zheng; Xuwen Wu; Wei-Guang Yang; Bai-Xue Li; Kejing Gao; Jingsheng Zhou; Yunfang Liu; Dongzhi Yang (Journal of Hazardous Materials, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Preparation and evaluation of an active modified oxygen/ carbon dioxide preservative for packaged fresh-cut durian - Guang Wu; Shuangdi Hou; Qingchun Yin; Li Guo; Hao Deng (Food Packaging and Shelf Life, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Metal–to–particle charge transfer invoked photoelectrochemistry on ferroelectric SrTiO3 for split–mode and high–throughput aptasensing - Qi Zhang; Mengmeng Gu; Lan Zhang; Xiuming Wu; Guang-Li Wang (Analytica Chimica Acta, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Cellulosic ethanol stillage for methane production by integrating single-chamber anaerobic digestion and microbial electrolysis cell system - Tian-Jie Ao; Jie Wu; Kai Li; Richard Chandra; Xin-Qing Zhao; Yue-Qin Tang; Chen-Guang Liu; Feng-Wu Bai (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

The effects of online-training artificial neural network mechanism and multi-stage parametric modeling method on simulation-based design system for ship optimization - Lin Du; Qin Wu; Yuehui Shu; Guang-nian Li (Ocean Engineering, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

The Khashir gabbro-tonalite suite in the Eastern Desert of Egypt: A root of a rifted Tonian oceanic arc system in the northwestern tip of the accretionary Arabian-Nubian orogen - Yasser Abd El-Rahman; Khamis Mekki; Li-Guang Wu; Xian-Hua Li; Mohamed Mabrouk (Lithos, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

Sliding connectors for cyclic construction of steel-UHPC composite truss arch bridges: design method and feasibility study - Guang He; Xudong Shao; Suiwen Wu; Junhui Cao; Panpan Li; Wenyong Cai (Engineering Structures, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Synergistic effect of holey graphene and CoSe2-NiSe2 heterostructure to enhance fast Na-ion transport - Chong Xu; Kaiyi Chen; Jiahao Yang; Guang Ma; Ye Wang; Zizheng Zhou; Zhixuan Wu; Sai Che; Zechen Li; Yuxin Tu; Zhihua Xiao; Daqiang Jiang; et al. (Chemical Engineering Journal, 2024)

CoSe2-Modified multidimensional porous carbon frameworks as high-Performance anode for fast-Charging sodium-Ion batteries - Chong Xu; Jiahao Yang; Kaiyi Chen; Guang Ma; Ye Wang; Zechen Li; Zizheng Zhou; Zhixuan Wu; Sai Che; Changsheng Ding; Yongfeng Li (Chemical Engineering Journal, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Stereo visual-inertial localization algorithm for orchard robots based on point-line features - Xing Xu; Jinming Liang; Jianying Li; Guang Wu; Jieli Duan; Mohui Jin; Han Fu (Computers and Electronics in Agriculture, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Cadmium stress induces gut microbiota imbalance and consequent activation of the gut–liver axis leading to liver injury and inflammation response in largemouth bass (Micropterus salmoides) - Li Jiang; Qiuhong Wu; Songsong Bao; Guang Fan; Zhiwen Yang; Pan Zhou; Xiaofei Yang; Xinyue Liu; Xinhong Zhou; Yachao Wang (Frontiers in Marine Science, 2024)
Introduction In recent years, cadmium pollution has increasingly serious impacts on aquatic environments, directly threatening the health and growth of freshwater fish and causing significant economic losses to the aquaculture industry. However, there is limited research on the effects of cadmium on the gut-liver axis and hepatotoxicity in freshwater fish. Therefore, this study investigated the potential toxic effects of cadmium induction through the gut-liver axis on largemouth bass. Methods This experiment was divided into four groups, each with different concentrations of cadmium solution added to the water (0.00 mg/L, 1.024 mg/L, 1.537 mg/L, 2.306 mg/L), with three replicates per group, and a feeding period of 42 days. Results and discussion The research findings indicate a significant decline in the growth performance of largemouth bass under cadmium stress (P<0.05). Cadmium-induced oxidative stress inhibited the activity of antioxidant enzymes, activated the Nrf2-Keap1 antioxidant pathway, resulting in increased levels of MDA and ROS, and decreased activities of CAT, GSH-PX, and SOD antioxidant enzymes, as well as related gene expressions (P<0.05). Additionally, cadmium down-regulated the expression of IL-10 and up-regulated the expression of IL-15, IL-8, IL-1β, TNF-α, and MT, indicating an inflammatory response in the liver (P<0.05). Tissue section observations after cadmium stress revealed hepatocyte nuclear condensation, cell degeneration, necrosis, and vacuolization, as well as shortened intestinal villi and intestinal epithelial cell metaplasia. Furthermore, cadmium down-regulated the expression of intestinal barrier-related proteins ZO-1 and Occludin (P<0.05), reducing intestinal microbial diversity. Correlation analysis revealed a close relationship between intestinal microbiota and hepatic immune factors. In summary, cadmium stress can disrupt the intestinal barrier, alter the structure of intestinal microbiota, and the gut-liver axis may potentially play a role in the toxicity of intestinal microbiota and liver.

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Quartz trace element geochemistry and internal morphology as proxies for provenance characterization: Results from the Marwar basin, NW India - Jun Zhang; Rui Li; Manoj K. Pandit; Ting-Guang Lan; Qing Xiong; Yuan-Bao Wu; Jun-Hong Zhao; Wei Wang (Precambrian Research, 2024)

Multi‐omics analyses reveal the signatures of metabolite transfers across trophic levels in a high‐ CO 2 ocean - Mengcheng Ye; Jiale Zhang; Mengting Xiao; Jiali Huang; Yunyue Zhou; John Beardall; John A. Raven; Guang Gao; Xiao Liang; Fenghuang Wu; Baoyi Peng; Leyao Xu; et al. (Limnology and Oceanography, 2024)
Although the diverse impacts of elevated dissolved CO 2 and warming on organisms within various trophic levels in marine food webs are well documented, we have yet to explore the biological links across different levels of biological organization from primary producers to secondary producers on an evolutionary time scale in a high‐CO 2 ocean. Here, we cultured a model marine diatom Phaeodactylum tricornutum (primary producer) in predicted future high‐CO 2 and/or warming conditions for ~ 1250 d with an experimental evolution approach and then fed them to the clam Coelomactra antiquata (secondary producer). We present an in‐depth multi‐omics analysis along the methylome (primary producer)–transcriptome (primary producer)–metabolome (primary producer)–metabolome (secondary producer) continuum. Our results showed that the downregulated terpenoid backbone biosynthesis in the methylome and transcriptome lead to decreased pyruvate levels and upregulation of some pathways (such as phenylalanine metabolism) in the metabolome of the primary producer in the long‐term warming conditions. These changes in metabolomic profile in the primary producer were then transferred to the secondary producer, resulting in changes in abundance of some metabolites, such as decreases in pyruvate, and in pyruvaldhyde (also known as methylglyoxal), and increases in 2‐hydroxylamino‐4,6‐dinitrotoluene. Our study provides a new insight into the molecular mechanisms underlying the trophic transfer from primary to secondary producers in a future high‐CO 2 ocean and may provide more accurate projections of marine ecosystem services and functions over the next century.

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Ultrasmall copper nanodots eye drops for microenvironment regulation of diabetes retinopathy by relieving hypoxia and inhibiting HIF-1α/VEGF signaling pathway - Min Tian; Zheng Li; Siyan Liu; Zhiyuan Wang; Bo Deng; Yang Cao; Jinchuan Wu; Zhu Zhu; Jun Jiang; Guang Li; Hongbin Lv (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Microbial contribution to 14 biogenic amines accumulation in refrigerated raw and deep-fried hairtails (Trichiurus lepturus) - Hao Deng; Guang Wu; Lingyu Zhou; Xiaomei Chen; Li Guo; Senlin Luo; Qingchun Yin (Food Chemistry, 2024)

Linear and nonlinear rheological characterization of capillary protein oleogels as potential fat replacers: Comparison with high internal-phase emulsions - Gao-Shang Wang; Qing Li; Guang-Xin Feng; Chuan-Wu Han; Jian Guo; Jin-Mei Wang; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Systems metabolic engineering of Corynebacterium glutamicum to assimilate formic acid for biomass accumulation and succinic acid production - Kai Li; Xue Zhang; Cheng Li; Yu-Cheng Liang; Xin-Qing Zhao; Chen-Guang Liu; Anthony J. Sinskey; Feng-Wu Bai (Bioresource Technology, 2024)

Advances in ice avalanches on the Tibetan Plateau - Minggao Tang; Guang Li; Huanle Zhao; Qiang Xu; Guangjian Wu; Wei Yang; Daojing Guo (Journal of Mountain Science, 2024)

Effects of benzophenone-3 and its metabolites on the marine diatom Chaetoceros neogracilis: Underlying mechanisms and environmental implications - Yi Yang; Guang-Jie Zhou; Ziying Li; Jiaji Sun; Alice Sze Tsai Wong; Vincent Chi Chiu Ko; Rudolf Shiu Sun Wu; Keng Po Lai (Science of The Total Environment, 2024)

Corrigendum to “Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface” [Ocean Eng. 297, April 2024] - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Remobilization of carbon in the lithospheric mantle during decratonization - Ya-Dong Wu; Jin-Hui Yang; Vadim S. Kamenetsky; Hao Wang; Xiao-Guang Li (Lithos, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Prolonged evolution of syn-collisional progressive deformation of the Trans-North China Orogen: Structural and geochronological evidence from the Xiaoqinling region, central China - Yunjian Li; Guang Zhu; Chengchuan Gu; Cheng Liu; Shuai Zhang; Xiaodong Wu; Tian Zhao; Chao Li; Menglong Dong (Gondwana Research, 2024)

Recent development of carrier materials in anthocyanins encapsulation applications: A comprehensive literature review - Ze Fu; Hao Ju; Guang-Sen Xu; Yan-Chao Wu; Xiao Chen; Hui-Jing Li (Food Chemistry, 2024)

Rapid and facile detection of largemouth bass ranavirus with CRISPR/Cas13a - Min Guang; Qian Zhang; Ruige Chen; Huaming Li; Mengran Xu; Xiaomin Wu; Rongrong Yang; HongBo Wei; Linzhu Ren; Liancheng Lei; Fuxian Zhang (Fish & Shellfish Immunology, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Advancing rehabilitation: Knittable fiber-shaped sensors for monitoring rotator cuff injury recovery - Han Zhang; Guang Li; Huidan Wei; Xuechen Wu; Sai Yan; Yuhan Xia; Shengyuan Yang; Patrik Schmuki; Ran Cao; Meifang Zhu (Chemical Engineering Journal, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Salinity controlling enhanced high-salinity pickle wastewater treatment coupling with high-value fatty acid production by Dunaliella salina - Hao Hu; Bang-Lei Wu; Dong Wei; Li Yu; Wei-Hua Li; Shu-Guang Zhu (Journal of Cleaner Production, 2024)

TFN nanofiltration membrane incorporating ZIF-8@MXene for efficient removal ReO4- from simulated nuclear-contaminated wastewater - Ning-xiao Wei; Yu-xing Wang; Hua-li Chen; Li-guang Wu; Ting Wang (Journal of Environmental Chemical Engineering, 2024)

Study on formation of methane hydrate in rotating packed bed - Jian-Lu Zhu; Nan Li; Yu-Xing Li; Wu-Chang Wang; Guang-Chun Song; Hui Han; Yun-Fei Wang (Fuel, 2024)

Spatiotemporal evolution of county level ecological security based on an emergy ecological footprint model: The case of Dingxi, China - Yanhua Lu; Lijuan Yan; Jie Li; Yunliang Liang; Chuanjie Yang; Guang Li; Jiangqi Wu; Hua Xu (Ecological Modelling, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Phosphorus doped carbon coated palygorskite interlayer and its polysulfides fixation behavior - Kailong Zhang; Luanhui Wu; Chao Zhang; Qidong Yang; Wei Qian; Jiadong Zhang; Guang Hu; Weiwei Hu; Yazhou Kong; Zhihui Wang; Liangbiao Wang; Gaoran Li; et al. (Applied Clay Science, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Flow condensation heat transfer correlation development of R32-oil mixture inside a micro-fin tube - Bao Yue; Guang Li; Jianfeng Li; Zhigang Wu; Hao Zhang; Yanpo Shao; Dawei Zhuang; Guoliang Ding; Xiaomin Weng; Zhuang Zhou (International Journal of Refrigeration, 2024)

A dual-functional lignin containing pulp foam for solar evaporation and contaminant adsorption - Yidong Zhang; Wangfang Deng; Meiyan Wu; Chao Liu; Guang Yu; Qiu Cui; Pedram Fatehi; Chunlin Xu; Bin Li (Desalination, 2024)

Enlightening thermoelectric mastery: Bio-inspired cellulose gel containing eco-friendly deep eutectic solvents - Yuxi Chen; Gonghua Hong; Lei Li; Qing Qu; Guang Li; Jiajie Wu; Lin Ge (Chemical Engineering Journal, 2024)

Effect of SARS-CoV-2 infection in early pregnancy on placental development - Shanru Yi; Liping Wang; Mengting Wang; Wei Hong; Ben Xu; Xiaoying He; Mengtian Yang; Zhiping Wu; Beiying Wang; Guang Yang; Shijun Shen; Xinyu Cui; et al. (Science China Life Sciences, 2024)

Reinitiation of modern-style plate tectonics in the Early Neoproterozoic: Evidence from a ∼930 Ma blueschist-facies terrane in South China - Li-Guang Wu; Yi Chen; Richard M. Palin; Qiu-Li Li; Lei Zhao; Yi-Bing Li; Chao-Feng Li; You-Lian Li; Xian-Hua Li (Precambrian Research, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Optimizing biochar application rates for improved soil chemical environments in cotton and sugarbeet fields under trickle irrigation with plastic mulch - Xingyun Qi; Guang Yang; Yi Li; Zhenan Hou; Penghui Shi; Shibin Wang; Xiaofang Wang; Jiaping Liang; Benhua Sun; Kadambot H.M. Siddique; Shufang Wu; Hao Feng; et al. (Soil and Tillage Research, 2024)

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Embryonic exposure of polystyrene nanoplastics affects cardiac development - Jingyan Li; Huimin Weng; Shuang Liu; Fan Li; Ke Xu; Shan Wen; Xi Chen; Chang Li; Yongmei Nie; Bin Liao; Jianming Wu; Fahsai Kantawong; et al. (Science of The Total Environment, 2024)

Petrogenesis and implications for tin mineralization of the Beidashan granitic pluton, southern Great Xing'an Range, NE China: Constraints from whole-rock and accessory mineral geochemistry - Fei Yang; Guang Wu; Gongzheng Chen; Shihui Li; Yinglei Li; Tong Zhang; Yanjing Chen (Journal of Asian Earth Sciences, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

RuO2/CeO2 heterostructure anchored on carbon spheres as a bifunctional electrocatalyst for efficient water splitting in acidic media - Yun Wu; Rui Yao; Kaiyang Zhang; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Integrative application of biochar and arbuscular mycorrhizal fungi for enhanced chromium resistance in Medicago sativa - Jinglong Li; Gengxue Fu; Shuping Xing; Baodong Chen; Songlin Wu; Haiyan Feng; Guang Yang; Yaoyu Zhou; Xin Zhang (Science of The Total Environment, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Transformation from Knudsen diffusion to facilitated diffusion for CO2 in confined mass transfer channels of polyimide mixed matrix membranes - Ting Wang; Ke Zhang; Shi-wen Du; Li-guang Wu; Chun-juan Li; Hua-li Chen; Hai-Chang Guo (Chemical Engineering Journal, 2023)

The Anterior Insula and its Projection to the Prelimbic Cortex are Involved in the Regulation of 5-HT-Induced Itch - Juan Yao; Xuan Li; Guang-Yan Wu; Bing Wu; Jun-Hui Long; Pu-Jun Wang; Shu-Lei Liu; Jie Gao; Jian-Feng Sui (Neuroscience Bulletin, 2023)
Itch is an unpleasant sensation that urges people and animals to scratch. Neuroimaging studies on itch have yielded extensive correlations with diverse cortical and subcortical regions, including the insular lobe. However, the role and functional specificity of the insular cortex (IC) and its subdivisions in itch mediation remains unclear. Here, we demonstrated by immunohistochemistry and fiber photometry tests, that neurons in both the anterior insular cortex (AIC) and the posterior insular cortex (PIC) are activated during acute itch processes. Pharmacogenetic experiments revealed that nonselective inhibition of global AIC neurons, or selective inhibition of the activity of glutaminergic neurons in the AIC, reduced the scratching behaviors induced by intradermal injection of 5-hydroxytryptamine (5-HT), but not those induced by compound 48/80. However, both nonselective inhibition of global PIC neurons and selective inhibition of glutaminergic neurons in the PIC failed to affect the itching-scratching behaviors induced by either 5-HT or compound 48/80. In addition, pharmacogenetic inhibition of AIC glutaminergic neurons effectively blocked itch-associated conditioned place aversion behavior, and inhibition of AIC glutaminergic neurons projecting to the prelimbic cortex significantly suppressed 5-HT-evoked scratching. These findings provide preliminary evidence that the AIC is involved, at least partially via aversive emotion mediation, in the regulation of 5-HT-, but not compound 48/80-induced itch.

Hidden dangers of ice avalanches and glacier lake outburst floods on the Tibetan Plateau: identification, inventory, and distribution - Minggao Tang; Qiang Xu; Lina Wang; Huanle Zhao; Guangjian Wu; Jian Zhou; Guang Li; Wenjing Cai; Xu Chen (Landslides, 2023)

Assessment of genetic diversity of Prunus salicina 'Shazikongxinli' by morphological traits and molecular markers - Gui Wang; Ruirui Li; Maohong Wu; Feihong Ren; Lili Wang; Guang Qiao (Genetic Resources and Crop Evolution, 2023)

Simulation and prediction of the geographical distribution of five Caragana species in the north temperate zone - Xiuchen Jiang; Linxuan Wu; Guang Yang; Yike Gao; He Li (Environmental Monitoring and Assessment, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

A novel C-type lectin (SpccCTL) suppresses MCRV replication by binding viral protein and regulating antiviral peptides in Scylla paramamosain - Qing-Feng Yang; Shouhu Li; Guang-Peng Feng; Chuang Qin; Xiu-Wen Min; Wen-Hong Fang; Yue Wu; Jin Zhou; Xin-Cang Li (Fish & Shellfish Immunology, 2023)

Inorganic Nanoparticles–Driven Self–Assembly of natural small molecules in water for constructing multifunctional nanocapsules against plant diseases - Li-Wei Liu; Zheng-Hao Ding; Gang-Gang Ren; Guang-Di Wang; Xin Pan; Guo-Hai Wei; Xiang Zhou; Zhi-Bing Wu; Zhi-Chao Jin; Yonggui Robin Chi; Song Yang (Chemical Engineering Journal, 2023)

Effects of the core heading date genes Hd1, Ghd7, DTH8, and PRR37 on yield-related traits in rice - Kangli Sun; Wubei Zong; Dongdong Xiao; Zeqiang Wu; Xiaotong Guo; Fuquan Li; Yingang Song; Shengting Li; Guangliang Wei; Yu Hao; Bingqun Xu; Weitao Li; et al. (Theoretical and Applied Genetics, 2023)

Effects of nitrogen deposition on N2O emission in a wet meadow on the Qinghai-Tibet Plateau - Jiangqi Wu; Haiyan Wang; Guang Li (Applied Soil Ecology, 2023)

Phenethylamine Is a Potential Density Stress Pheromone in Turbot (Scophthalmus maximus) - Jiyuan Li; Yanfeng Wang; Teng Guo; Shihong Xu; Guang Gao; Feng Liu; Xiaoyang Guo; Yanduo Wu; Haixia Zhao; Jun Li (Fishes, 2023)
Pheromones play a vital role in regulating fish behavior, including reproduction, aggregation, hazard recognition and food location. To gain a better understanding of chemical communication in fish produced by density changes, this study analyzed the metabolites released by turbot (Scophthalmus maximus) under different stocking densities. The experiment was conducted at low (LD: 3.01 kg/m2), medium (MD: 6.62 kg/m2) and high (HD: 10.84 kg/m2) densities for 15 days. High-throughput non-targeted metabolomics (LC-MS/MS) was used to identify variations in metabolites released into the aquatic environment by turbot at different densities. Results showed that 29 and 47 metabolites were significantly upregulated in the MD and HD groups, respectively, compared with the LD group. Among them, hexadecanedioic acid, xanthine, phenethylamine, proline and styrene were significantly upregulated in the MD vs. LD, HD vs. MD and HD vs. LD. The VIP diagram of OPLS-DA alignment showed that phenethylamine was the most important metabolite shared by MD vs. LD, HD vs. MD and HD vs. LD. Key gene changes in the GH/IGF-1 signaling pathway, HPI axis of turbot were studied using qRT-PCR for density treatment. The results demonstrated that the expression of GH, GHR and IGF-1 was significantly lower, while the expression of CRH and ACTH was higher in the HD group. Additionally, plasma levels of cortisol, glucose, triglycerides and T3 were also highest in the HD group compared with the LD and MD groups. Phenylethylamine concentration was positively correlated with the HPI axis and negatively correlated with the GH/IGF-1 signaling pathway. To investigate the impact of phenethylamine accumulation on turbot, an acute treatment experiment with phenethylamine was set up. Its concentration in the aquatic environment was set at 0 (CON), 10−7 (LP) and 10−5 (HP) mol/L via exogenous addition, and turbot were exposed to these environments for 2 days. There was a high degree of concordance between the GH/IGF-1 signaling pathway (GH, GHR, IGF-1), HPI axis (CRH, ACTH) and plasma physiological changes (cortisol, glucose, triglycerides, T3) in the phenethylamine-treated group and the density-treated group. Therefore, accumulation of phenethylamine with increasing stocking density may be a potential cause of density stress. Phenylethylamine has a dose-dependent and trace effect as a pheromone.

Polystyrene nanoplastics induce apoptosis of human kidney proximal tubular epithelial cells via oxidative stress and MAPK signaling pathways - Zhu Zhu; Ruixue Liao; Yang Shi; Jingyan Li; Jimin Cao; Bin Liao; Jianming Wu; Guang Li (Environmental Science and Pollution Research, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Heavy silicon and oxygen isotope signatures of TTGs formed in distinct tectonic settings - Kai Lei; Qing Zhang; Yu Liu; Kai Lu; Li-Guang Wu; Sheng He; Xian-Hua Li (Precambrian Research, 2023)

Deep transfer learning based on transformer for flood forecasting in data-sparse basins - Yuanhao Xu; Kairong Lin; Caihong Hu; Shuli Wang; Qiang Wu; Li Zhang; Guang Ran (Journal of Hydrology, 2023)

Neoproterozoic crustal growth and reworking in South Qinling, central China: Evidence from zircon U-Pb age and Hf isotopic composition of paragneiss in the Foping dome - He Zhang; Jun He; Yan-Chen Li; Guang-Hui Wu; Hong Cheng; Fukun Chen (Journal of Asian Earth Sciences, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Developing high-dimensional machine learning models to improve generalization ability and overcome data insufficiency for mixed sugar fermentation simulation - Xiao-Yan Huang; Tian-Jie Ao; Xue Zhang; Kai Li; Xin-Qing Zhao; Verawat Champreda; Weerawat Runguphan; Chularat Sakdaronnarong; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Diverse diterpenoids from Callicarpa rubella Lindl. as natural inhibitors of macrophage foam cell formation - Xue-Wen Wu; Qian-Lang Feng; Yi-Fan Xie; Si-Chen Song; Bin Cheng; Yan Ma; Qing Li; Xu Ji; Xiao-Li Li; Guang Cao; Wei-Lie Xiao (Phytochemistry, 2023)

Geochemical characteristics of the Chang 7 Member in the southwestern Ordos Basin, China: the influence of sedimentary environment on the organic matter enrichment - Chen Li; Shi-Jia Chen; Jian-Bo Liao; Yu-Ting Hou; Jian Yu; Guang-Lin Liu; Kun Xu; Xue-Ting Wu (Palaeoworld, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Tonian-Cryogenian bimodal volcanism and related sulfide ores in the Arabian-Nubian Shield: An example from the Dendekan prospect in the Eastern Desert of Egypt - Yasser Abd El-Rahman; Mohamed Ramzey; Li-Guang Wu; Xian-Hua Li; Moataz El-Shafeiy; Amir Said (Geochemistry, 2023)

A novel machine learning-based model predictive control framework for improving the energy efficiency of air-conditioning systems - Sihao Chen; Puxian Ding; Guang Zhou; Xiaoqing Zhou; Jing Li; Liangzhu (Leon) Wang; Huijun Wu; Chengliang Fan; Jiangbo Li (Energy and Buildings, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of nitrogen and phosphorus additions on CH4 flux in wet meadow of Qinghai-Tibet Plateau - Jiangqi Wu; Yanhua Lu; Haiyan Wang; Guang Li (Science of The Total Environment, 2023)

Quantitative assessment of the effects of zeolite alteration processes on deep clastic reservoirs – A case study of the Jiamuhe Formation in the Shawan Sag, Junggar Basin, China - Junjun Zhou; Haiguang Wu; Jian Wang; Guang Hu; Yunfeng Zhang; Jinlai Feng; Yilin Li (Marine and Petroleum Geology, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

Unprecedented spirodioxynaphthalenes from the endophytic fungus Phyllosticta ligustricola HDF-L-2 derived from the endangered conifer Pseudotsuga gaussenii - Hao-Wei Chen; Chun-Xiao Jiang; Guang-Lei Ma; Xi-Ying Wu; Wei Jiang; Jiyang Li; Yi Zang; Jia Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2023)

A comprehensive performance evaluation methodology for sea-crossing cable-stayed bridges under wind and wave loads - Chao Li; Guo-Yi Wu; Lu-Xi Li; Chun-Guang Liu; Hong-Nan Li; Qiang Han (Ocean Engineering, 2023)

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Removal of antibiotic resistant bacteria and genes by nanoscale zero-valent iron activated persulfate: Implication for the contribution of pH decrease - Chun-shuang Zhou; Guang-li Cao; Xiu-Kun Wu; Bing-feng Liu; Qing-Yue Qi; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Experimental study on coal combustion by using the ilmenite ore as active bed material in a 0.3 MWth circulating fluidized bed - Lin Li; Junhua Mao; Wu Tang; Guang Sun; Quanbin Gu; Xiaoyan Lu; Ke Shao; Yuqing Chen; Lunbo Duan (Fuel, 2023)

Engineering Corynebacterium glutamicum for efficient production of succinic acid from corn stover pretreated by concentrated-alkali under steam-assistant conditions - Kai Li; Cheng Li; Xin-Qing Zhao; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2023)

Distinct tectono-magmatism on the margins of Rodinia and Gondwana - Guang-Hui Wu; Xu Chu; Ming Tang; Weiyong Li; Fukun Chen (Earth and Planetary Science Letters, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Understanding the effects of the electrochemical and thermal properties of the separator on the battery temperature - Yue Lu; Zonglin Wu; Guang Cheng; T.A. Venkatesh; Gaojun Liu; Yaozong Bai; Le Yu; Nianwu Li (Chemical Engineering Journal, 2023)

In situ rapid and deep self-reconstruction of Fe-doped hydrate NiMoO4 for stable water oxidation at high current densities - Yijie Zhang; Rui Yao; Yun Wu; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

A novel label-free dual-mode aptasensor based on the mutual regulation of silver nanoclusters and MoSe2 nanosheets for reliable detection of ampicillin - Pengfei Fan; Xin Qian; Qianji Li; Ping Jiang; Qian Wu; Guang Huang; Zhan Zhang; Lei Li (Analytica Chimica Acta, 2023)

In situ formed and switchable enzymatic activity of BiOBr under light stimulation for homogeneous and label-free bioassay - Lan Zhang; Xin Gao; Qi Zhang; Xiuming Wu; Guang-Li Wang (Analytica Chimica Acta, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Theoretically thermal-varying models of the neutral axis position for local damage detection of bridge girders - Guang-Ming Wu; Sheng-Li Li; Ting-Hua Yi; Xiu-Dao Mei; Ya-Fei Wang (Engineering Structures, 2023)

Friction anomaly alarm for bridge sliding bearings under operating environmental conditions - Guang-Ming Wu; Ting-Hua Yi; Dong-Hui Yang; Hong-Nan Li; Hua Liu (Engineering Structures, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Dual electrical-behavior regulation of α-MoC quantum dots and Mo-N-C sites for high photoelectric conversion performance of solar cells - Jixin Yao; Wen Wang; Jie Wang; Shiwei Wu; Ying Meng; Shibin Lu; Haibo Wang; Feng Du; Bo Yang; Dongmeng Chen; Huaibao Tang; Haifeng Xu; et al. (Chemical Engineering Journal, 2023)

Bioregulation of FeNi LDH morphology and electronic structure to highly promote electrocatalytic oxygen evolution - Guang Li; Chang Liu; Yun Yang; Xiuwen Pan; Tao Wu; Feng Zeng; Enyang Ma; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

Nitrogen and phosphorus co-doped porous carbons (NPCs) for peroxydisulfate (PDS) activation towards tetracycline degradation: Defects enhanced adsorption and non-radical mechanism dominated by electron transfer - Minxian Cheng; Yichu Zhang; Bo Lai; Lingzhen Wang; Shengjiong Yang; Kailong Li; Dongqi Wang; Yaoguo Wu; Guang-Hao Chen; Jin Qian (Chemical Engineering Journal, 2023)

Facile synthesis of Fe3C-dominated Fe/Fe3C/FeN0.0324 multiphase nanocrystals embedded in nitrogen-modified graphitized carbon as efficient pH-universal catalyst for oxygen reduction reaction and zinc-air battery - Guang Li; Kuang Sheng; Yu Lei; Juan Yang; Yulian Chen; Xiaowei Guo; Gairong Chen; Baobao Chang; Tianjing Wu; Xianyou Wang (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

An inhibitory effect of schisandrone on α-hemolysin expression to combat methicillin-resistant staphylococcus aureus infections - Yingxin Qi; Juan Hou; Yicheng Zhao; Wu Song; Li Wang; Huan Chen; Guang Chen (World Journal of Microbiology and Biotechnology, 2023)

Establishment of adventitious root culture system of Cynanchum wilfordii in air-lift bioreactors for the efficient production of bioactive compounds - Mei Wang; Miao Wang; Dong An; Chun-Hua Wu; Guang Li; Wei Wang; Xiao-Song Zhang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Failure criteria of unreinforced masonry walls of rural buildings under the impact of flash floods in mountainous regions - Guang-wu Si; Xiao-qing Chen; Jian-gang Chen; Wan-yu Zhao; Shuai Li; Xiang-ning Li (Journal of Mountain Science, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Ice-Water-Gas Interaction during Icebreaking by an Airgun Bubble - Qi-Gang Wu; Zuo-Cheng Wang; Bao-Yu Ni; Guang-Yu Yuan; Yuriy A. Semenov; Zhi-Yuan Li; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2022)
When an airgun releases high-pressure gas underwater below an ice plate, it is observed that a bubble is formed rapidly while the ice plate is broken fiercely. In order to study the ice-water-gas interaction during this transient and violent phenomenon, a set of laboratory-scale devices was designed and a series of icebreaking experiments were carried out. High-speed photography was used to capture the evolution of the bubble and the ice plate. It was found that the airgun bubble had a unique ‘pear’ shape compared with the spherical bubble generated by electric sparking. The pressure induced by the pulsation of the airgun bubble near a rigid wall was measured by the pressure sensor. The initial shockwave, oscillatory pressure peaks caused by the directional fast air injection, secondary shockwave, and pressure peak caused by the bubble jet impact were clearly recorded. Three damage patterns of ice plates were observed and corresponding reasons were analyzed. The influence of dimensionless parameters, such as airgun-ice distance H and ice thickness T, was also investigated. The physical mechanism of ice-water-gas interaction was summarized.

Effects of Simulated Nitrogen Deposition on Soil Active Carbon Fractions in a Wet Meadow in the Qinghai-Tibet Plateau - Haiyan Wang; Jiangqi Wu; Guang Li; Lijuan Yan; Xingxing Wei; Weiwei Ma (Journal of Soil Science and Plant Nutrition, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

Effects of Plant Community Type on Soil Methane Flux in Semiarid Loess Hilly Region, Central Gansu Province, China - Chuanjie Yang; Guang Li; Lijuan Yan; Weiwei Ma; Jiangqi Wu; Yan Tan; Shuainan Liu; Shikang Zhang (Advances in Atmospheric Sciences, 2022)

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Phomopsis liquidambaris Increases Rice Mineral Uptake Under Waterlogging Condition via the Formation of Well-Developed Root Aerenchyma - Li-Yan Hu; Yang Yang; Hao Wu; Meng-Jun Tang; Xing-Guang Xie; Chuan-Chao Dai (Journal of Plant Growth Regulation, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Effects of rainfall frequency on soil labile carbon fractions in a wet meadow on the Qinghai-Tibet Plateau - Haiyan Wang; Jiangqi Wu; Guang Li; Lijuan Yan; Xingxing Wei (Journal of Soils and Sediments, 2022)

Targeting GATA1 and p2x7r Locus Binding in Spinal Astrocytes Suppresses Chronic Visceral Pain by Promoting DNA Demethylation - Yan-Yan Wu; Hai-Long Zhang; Xiaomin Lu; Han Du; Yong-Chang Li; Ping-An Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2022)
Irritable bowel syndrome is a gastrointestinal disorder of unknown etiology characterized by widespread, chronic abdominal pain associated with altered bowel movements. Increasing amounts of evidence indicate that injury and inflammation during the neonatal period have long-term effects on tissue structure and function in the adult that may predispose to gastrointestinal diseases. In this study we aimed to investigate how the epigenetic regulation of DNA demethylation of the p2x7r locus guided by the transcription factor GATA binding protein 1 (GATA1) in spinal astrocytes affects chronic visceral pain in adult rats with neonatal colonic inflammation (NCI). The spinal GATA1 targeting to DNA demethylation of p2x7r locus in these rats was assessed by assessing GATA1 function with luciferase assay, chromatin immunoprecipitation, patch clamp, and interference in vitro and in vivo . In addition, a decoy oligodeoxynucleotide was designed and applied to determine the influence of GATA1 on the DNA methylation of a p2x7r CpG island. We showed that NCI caused the induction of GATA1, Ten-eleven translocation 3 (TET3), and purinergic receptors (P2X7Rs) in astrocytes of the spinal dorsal horn, and demonstrated that inhibiting these molecules markedly increased the pain threshold, inhibited the activation of astrocytes, and decreased the spinal sEPSC frequency. NCI also markedly demethylated the p2x7r locus in a manner dependent on the enhancement of both a GATA1–TET3 physical interaction and GATA1 binding at the p2x7r promoter. Importantly, we showed that demethylation of the p2x7r locus (and the attendant increase in P2X7R expression) was reversed upon knockdown of GATA1 or TET3 expression, and demonstrated that a decoy oligodeoxynucleotide that selectively blocked the GATA1 binding site increased the methylation of a CpG island in the p2x7r promoter. These results demonstrate that chronic visceral pain is mediated synergistically by GATA1 and TET3 via a DNA-demethylation mechanism that controls p2x7r transcription in spinal dorsal horn astrocytes, and provide a potential therapeutic strategy by targeting GATA1 and p2x7r locus binding.

Effective connectivity decreases in specific brain networks with postparalysis facial synkinesis: a dynamic causal modeling study - Zhen-Zhen Ma; Ye-Chen Lu; Jia-Jia Wu; Xu-Yun Hua; Si-Si Li; Wei Ding; Jian-Guang Xu (Brain Imaging and Behavior, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Geochronology and geochemistry of Early Cretaceous bimodal volcanic rocks from Erguna Massif, NE China: evidence for the back-arc extension of the Mongol–Okhotsk orogenic belt - Fei Yang; Gong-Zheng Chen; Guang Wu; Ying-Lei Li; Yong-Xu Shao; Tie-Gang Li; Guang-Chao Song; Bing Han (International Journal of Earth Sciences, 2022)

Altered resting-state functional networks in patients with premenstrual syndrome: a graph-theoretical based study - Chengxiang Liu; Chunmei Xuan; Jiayu Wu; Shasha Li; Guang Yang; Ruiqing Piao; Gaoxiong Duan; Demao Deng; Peng Liu (Brain Imaging and Behavior, 2022)

Analysis of Pipeline Deformation Caused by Shield Tunnel Excavation that Obliquely Crosses Existing Pipelines - Sheng-Wu Zhao; Xiao-Li Li; Xin Li; Li-Guang Chen; Tong Li; Suo-Hui Li; Yu Bai (Arabian Journal of Geosciences, 2022)

The evolution of hydrochemical and isotopic signatures from precipitation, surface water to groundwater in a typical karst watershed, Central Texas, USA - Lijun Tian; Yongli Gao; Guang Yang; Benjamin Schwartz; Binggui Cai; Guoliang Lei; Guitao Shi; Christopher Ray; Soeuth Sok; Erica Martinez; Yunxia Li; Haibin Wu (Isotopes in Environmental and Health Studies, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Large-scale Late Triassic to Early Jurassic high εHf(t)–εNd(t) felsic rocks in the Ergun Massif (NE China): implications for southward subduction of the Mongol–Okhotsk oceanic slab and lateral crustal growth - Yinglei Li; Guang Wu; Shengjin Zhao; Gongzheng Chen; Fei Yang; Tiegang Li (International Journal of Earth Sciences, 2021)

First report of Chaetomella raphigera causing brown spot on Eucalyptus urophylla × E. grandis in China - Xiu-Xiu Cao; Ji-Guang Wei; Jian-Gan Hou; Chun-Li Fan; Ji Luo; Yao-Jun Wu; Xiu-Hao Yang; Ji-Tong Luo; Xiao-Bing Yang (Journal of Plant Pathology, 2021)

Knockdown of circPUM1 impedes cell growth, metastasis and glycolysis of papillary thyroid cancer via enhancing MAPK1 expression by serving as the sponge of miR-21-5p - Yanqi Li; Jun Qin; Zhaocai He; Guang Cui; Kun Zhang; Buqiang Wu (Genes & Genomics, 2021)

Multiple Fetal Nutritional Patterns Before Parturition in Viviparous Fish Sebastes schlegelii (Hilgendorf, 1880) - Du Tengfei; Xiao Yongshuang; Zhao Haixia; Zhou Li; Liu Qinghua; Wang Xueying; Li Jun; Xu Shihong; Wang Yanfeng; Yu Jiachen; Wu Lele; Wang Yunong; et al. (Frontiers in Marine Science, 2021)
Sebastes schlegelii is a commercially important fish with a special viviparous reproductive system that is cultured in near-shore seawater net cages in East Asia. In the gonadal development of the species, the gonad of males mature before those of females, which mature after mating. Mating in male/female fishes occurs in October of each year. Then, females undergoing oocyte maturation complete fertilization using stored sperm in March of the following year. The pregnancy is completed when larvae are produced in the ovary. It has been reported that embryonic nutrient supply originates entirely from the female viviparous reproductive systems. However, until now, the nutritional patterns and the processes of nutrient provision in S. schlegelii before parturition have not been clear. The goal of this research was to study the embryos, larvae and juveniles of S. schlegelii during pregnancy. Anatomical observations, light microscopy and scanning electron microscopy were used to study the developmental characteristics of early embryos and larvae and the connecting structures between the mother and the fetus. The results showed the following: (1) Placental-like structures were found during the process of embryonic development in S. schlegelii , and these placental-like structures proliferated after fertilization. (2) The embryos of S. schlegelii were encased by a saclike structure composed of blood vessels, connective tissue, and surface epithelial cells. The vessels near the embryo existed in the thecal layer. Vascularized proliferation was detected following embryonic development. (3) Starting in the gastrula stage, connections between the embryo and surrounding cells loosened, and ovarian fluid became abundant. In addition, a large number of small holes and cristae were observed on the surface of the embryo. We speculate that embryos may be able to absorb nutrients from the ovarian fluid. (4) Yolk was present throughout embryo development. (5) Two types of nutritional modes were observed, lecithotrophic and matrotrophic during embryonic development. Three forms of placental analogs may exist in S. schlegelii : (1) external epithelial absorptive surfaces; (2) trophonemata, with modifications of the ovarian epithelia for absorbing the histotroph; and (3) a follicular pseudoplacenta, with close apposition between follicle cells and embryonic absorptive epithelia.

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Characterization of Ogura CMS fertility-restored interspecific hybrids and backcross progenies from crosses between broccoli and rapeseed - Chun-qing Liu; Guang-qing Li; Xue-qin Yao; Lei Huang; Xin-yan Wu; Zhu-jie Xie (Euphytica, 2020)

Biological denitrification in a macrophytic lake: implications for macrophytes-dominated lake management in the north of China - Huan-guang Deng; Ju Zhang; Jin-jia Wu; Xin Yao; Li-wei Yang (Environmental Science and Pollution Research, 2020)

Identifying ephemeral gullies from high-resolution images and DEMs using flow-directional detection - Wen Dai; Guang-hui Hu; Xin Yang; Xian-wu Yang; Yi-han Cheng; Li-yang Xiong; Josef Strobl; Guo-an Tang (Journal of Mountain Science, 2020)

Multiple metal(loid)s bioaccessibility from cooked seafood and health risk assessment - Wen Liao; Wenbo Zhao; Ye Wu; Nan Rong; Xiaowei Liu; Kaiming Li; Guang Wang (Environmental Geochemistry and Health, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Three new phenylacetamide glycosides from Dracocephalum tanguticum Maxim and their anti-hyperglycemic activity - En-Guang Ma; Hai-Yan Wu; Li-Jiao Hu; Min Wei; Lin-Yun Mou; Gan-Peng Li (Natural Product Research, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Development of a specific AFLP-based SCAR marker for Chinese Race 34MKG of Puccinia graminis f. sp. tritici - Si Chen; Xue Yang; Wen-gong Huang; Yan Liu; Ying Yu; Guang-wen Wu; Shu-quan Zhang; Tian-ya Li; Yuan-yin Cao (Molecular Biology Reports, 2020)

The effects of emission trading system on corporate innovation and productivity-empirical evidence from China’s SO2 emission trading system - Hong-li Tang; Jian-min Liu; Jun Mao; Jin-guang Wu (Environmental Science and Pollution Research, 2020)

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

Alternation of back-arc extension and compression in an overriding plate: evidence from Cretaceous structures in the western Liaoning region, eastern China - Nan Su; Guang Zhu; Cheng Liu; Shuai Zhang; Yunjian Li; Hao Yin; Xiaodong Wu (International Journal of Earth Sciences, 2020)

Disruption of tight junction structure contributes to secretory dysfunction in IgG4-related sialadenitis - Sai-Nan Min; Li-Ling Wu; Yan-Yan Zhang; Wen-Xuan Zhu; Xin Cong; Guang-Yan Yu (Journal of Molecular Histology, 2020)

Zinc toxicity alters the photosynthetic response of red alga Pyropia yezoensis to ocean acidification - Jing Ma; Wen Wang; Xiaoyan Liu; Zhiqin Wang; Guang Gao; Hailong Wu; Xinshu Li; Juntian Xu (Environmental Science and Pollution Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

FadP affects the virulence of Ralstonia pseudosolanacearum by altering nitrogen metabolism processes and reducing motility, cellulase, and extracellular polysaccharide production - Jia-chun Wu; Min Zhong; Xing-wei Li; Cheng-peng Yu; Qiong-guang Liu (Journal of Plant Pathology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Early Cretaceous gold mineralization in the Lesser Xing’an Range of NE China: the Yongxin example - Zhong-Hai Zhao; Jing-Gui Sun; Guang-Hui Li; Wen-Xi Xu; Chang-Lu Lü; Song Wu; Yan Guo; Jin Liu; Liang Ren (International Geology Review, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Aldosterone stimulation mediates cardiac metabolism remodeling via Sirt1/AMPK signaling in canine model - Guang-zhong Liu; Song Zhang; Yan-yan Li; Yong-wu Liu; Yun Zhang; Xin-bo Zhao; Yue Yuan; Jia-wei Zhang; Zulfiia Khannanova; Yue Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Water quality prediction based on recurrent neural network and improved evidence theory: a case study of Qiantang River, China - Lei Li; Peng Jiang; Huan Xu; Guang Lin; Dong Guo; Hui Wu (Environmental Science and Pollution Research, 2019)

Antiproliferative activity of ursolic acid/glycyrrhetinic acid-uracil/thymine hybrids - Li Sun; Xiang-Wu Chu; Chun-mei Liu; Li-Xin Sheng; Zhuan-Xin Chen; Ke-Guang Cheng (Medicinal Chemistry Research, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

An updated phylogeny and diversity of Phylloporia (Hymenochaetales): eight new species and keys to species of the genus - Fang Wu; Guang-Juan Ren; Li Wang; José Ribamar C. Oliveira-Filho; Tatiana B. Gibertoni; Yu-Cheng Dai (Mycological Progress, 2019)

Pollution Characterization and Source Apportionment of Day and Night PM2.5 Samples in Urban and Suburban Communities of Tianjin (China) - Yan Zhao; Lihong Feng; Bodong Shang; Jianping Li; Guang Lv; Yinghong Wu (Archives of Environmental Contamination and Toxicology, 2019)

Endophytic community of Pb-Zn hyperaccumulator Arabis alpina and its role in host plants metal tolerance - Vijay K. Sharma; Xin-ya Li; Guang-li Wu; Wei-xiao Bai; Shobhika Parmar; James F. White Jr; Hai-yan Li (Plant and Soil, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Effect of Cooking on Speciation and In Vitro Bioaccessibility of Hg and As from Rice, Using Ordinary and Pressure Cookers - Wen Liao; Guang Wang; Kaiming Li; Wenbo Zhao; Ye Wu (Biological Trace Element Research, 2019)

The relative strength of different floral visitors driving floral evolution within a Primula secundiflora population - Yun Wu; Tao Zhong; Guang-Li Liu; Lu-Wei Tan; Qing-Jun Li (Evolutionary Ecology, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Expression of ASIC3 in the Trigeminal Nucleus Caudalis Plays a Role in a Rat Model of Recurrent Migraine - Sha Wang; Bai-Xue Wu; Chao-Yang Liu; Guang-Cheng Qin; Wen-Hui Yan; Ji-Ying Zhou; Li-Xue Chen (Journal of Molecular Neuroscience, 2018)

Thimet oligopeptidase and prolyl endopeptidase of spotted scat Scatophagus argus: characterization, tissue distribution, expression at different ovarian stages and down-regulation by estradiol - Si-ping Deng; Dong-neng Jiang; Jian-ye Liu; Zhi-qi Liang; Hua-pu Chen; Tian-li Wu; Chun-hua Zhu; Guang-li Li (Fisheries Science, 2018)

(−)-Epigallocatechin-3-gallate, the major green tea catechin, regulates the desensitization of β1 adrenoceptor via GRK2 in experimental heart failure - Qi Zhang; Liqun Hu; Li Chen; Hongqi Li; Jun Wu; Wenting Liu; Mengyuan Zhang; Guang Yan (Inflammopharmacology, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Geochronological and sedimentological evidences of Panyangshan foreland basin for tectonic control on the Late Paleozoic plate marginal orogenic belt along the northern margin of the North China Craton - Jialiang Li; Zhiguang Zhou; Yingfu He; Guosheng Wang; Chen Wu; Changfeng Liu; Guang Yao; Wentao Xu; Xiaoqi Zhao; Pengfei Dai (International Journal of Earth Sciences, 2018)

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

In Vitro-In Vivo Predictive Dissolution-Permeation-Absorption Dynamics of Highly Permeable Drug Extended-Release Tablets via Drug Dissolution/Absorption Simulating System and pH Alteration - Zi-qiang Li; Shuang Tian; Hui Gu; Zeng-guang Wu; Makafui Nyagblordzro; Guo Feng; Xin He (AAPS PharmSciTech, 2018)

An efficient and reusable quaternary ammonium fabric adsorbent prepared by radiation grafting for removal of Cr(VI) from wastewater - Li-juan Pang; Jiang-tao Hu; Mao-jiang Zhang; Chen-guang Yang; Guo-zhong Wu (Environmental Science and Pollution Research, 2018)

A 3-D DDA damage analysis of brick masonry buildings under the impact of boulders in mountainous areas - Shu-guang Liu; Zhu-jun Li; Hong Zhang; Wei Wu; Gui-hui Zhong; Sha Lou (Journal of Mountain Science, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

Knockdown of eukaryotic translation initiation factor 3 subunit D (eIF3D) inhibits proliferation of acute myeloid leukemia cells - Guo-zhen Liu; Ji-zhu Liu; Xiao-qing Li; Li Zhang; Shuang-jing Li; Tai-wu Xiao; Jing-xia Wang; Guang-yao Li; Yusen Liu (Molecular and Cellular Biochemistry, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

Spatial and temporal trends of reference crop evapotranspiration and its influential variables in Yangtze River Delta, eastern China - Yu Xu; Youpeng Xu; Yuefeng Wang; Lei Wu; Guang Li; Song Song (Theoretical and Applied Climatology, 2017)

Walnut anthracnose caused by Colletotrichum siamense in China - Qing-Hai Wang; Kun Fan; De-Wei Li; Shan-Guang Niu; Li-Qun Hou; Xiao-Qin Wu (Australasian Plant Pathology, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

A study of the damage of the intestinal mucosa barrier structure and function of Ctenopharyngodon idella with Aeromonas hydrophila - Wei-Guang Kong; Si-Si Li; Xiao-Xuan Chen; Yu-Qing Huang; Ying Tang; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2017)

Design, synthesis and cytotoxic evaluation of a novel series of benzo[d]thiazole-2-carboxamide derivatives as potential EGFR inhibitors - Lan Zhang; Xin-Shan Deng; Chao Zhang; Guang-Peng Meng; Jiao-Feng Wu; Xue-Song Li; Qing-Chun Zhao; Chun Hu (Medicinal Chemistry Research, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Erratum to: A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Evaluation of the antioxidant property and effects in Caenorhabditis elegans of Xiangxi flavor vinegar, a Hunan local traditional vinegar - Run-ting Huang; Qing Huang; Gen-liang Wu; Chun-guang Chen; Zong-jun Li (Journal of Zhejiang University-SCIENCE B, 2017)

Muscarinic acetylcholine receptor-mediated tight junction opening is involved in epiphora in late phase of submandibular gland transplantation - Ning-Yan Yang; Chong Ding; Jing Li; Yan Zhang; Ruo-Lan Xiang; Li-Ling Wu; Guang-Yan Yu; Xin Cong (Journal of Molecular Histology, 2017)

A Fluorescence Sensor for Lead (II) Ions Determination Based on Label-Free Gold Nanoparticles (GNPs)-DNAzyme Using Time-Gated Mode in Aqueous Solution - Xiao-Yu Wang; Cheng-Gang Niu; Li-Juan Guo; Liu-Yin Hu; Sheng-Quan Wu; Guang-Ming Zeng; Fei Li (Journal of Fluorescence, 2017)

Dating of the topmost terrace in the Jingxian Basin, Anhui Province: an indication of the establishment of the Qingyijiang River - Chun-sheng Hu; Chen-qi Hu; Shao-chen Liu; Guang-lai Xu; Li Wu; Li-hui Yang (Journal of Mountain Science, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Spatio-temporal assessments of rockburst hazard combining b values and seismic tomography - Jing Li; Si-Yuan Gong; Jiang He; Wu Cai; Guang-An Zhu; Chang-Bin Wang; Tian Chen (Acta Geophysica, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Reduction of soil-borne pathogen Fusarium solani reproduction in soil enriched with phenolic acids by inoculation of endophytic fungus Phomopsis liquidambari - Xing-Guang Xie; Chuan-Chao Dai; Xiao-Gang Li; Jia-Rui Wu; Qing-Qian Wu; Xing-Xiang Wang (BioControl, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Runoff coefficient characteristics and its dominant influencing factors in a riparian grassland in the Qinghai Lake watershed, NE Qinghai-Tibet Plateau - Zhou Li; Dong Liu; Xiao-Yan Li; Huawu Wu; Guang-Yong Li; Yue-Tan Li (Arabian Journal of Geosciences, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Newly discovered eclogites from the Bangong Meso–Tethyan suture zone (Gaize, central Tibet, western China): mineralogy, geochemistry, geochronology, and tectonic implications - Yu-Xiu Zhang; Zhi-Wu Li; Li-Dong Zhu; Kai-Jun Zhang; Wen-Guang Yang; Xin Jin (International Geology Review, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Analysis the role of arabidopsis CKRC6/ASA1 in auxin and cytokinin biosynthesis - Dong-Wei Di; Lei Wu; Pan Luo; Li Zhang; Tian-Zi Zhang; Xue Sun; Shao-Dong Wei; Chen-Wei An; Guang-Qin Guo (Journal of Plant Biology, 2016)

Chemical composition and antioxidant activities of the essential oil from Nandina domestica fruits - Shu-Feng Bi; Guang-Qi Zhu; Jie Wu; Zhong-Kang Li; Yong-Zhan Lv; Ling Fang (Natural Product Research, 2016)

Glutathione homeostasis and Cd tolerance in the Arabidopsis sultr1;1-sultr1;2 double mutant with limiting sulfate supply - Xiang Liu; Fei-Hua Wu; Jing-Xi Li; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Wen-Jun Hu; Li-Jie Gao; Zong-Ling Wang; Jun-Hui Chen; Martin Simon; Hai-Lei Zheng (Plant Cell Reports, 2016)

Single Chemosensor for Double Analytes: Spectrophotometric Sensing of Cu2+ and Fluorogenic Sensing of Al3+ Under Aqueous Conditions - Jie Yang; Ze-li Yuan; Guang-qing Yu; Shun-li He; Qing-hong Hu; Qing Wu; Bo Jiang; Gang Wei (Journal of Fluorescence, 2016)

RETRACTED ARTICLE: Effects of Common Polymorphisms in the MTHFR and ACE Genes on Diabetic Peripheral Neuropathy Progression: a Meta-Analysis - Shuai Wu; Yan Han; Qiang Hu; Xiao-Jie Zhang; Guang-Cheng Cui; Ze-Zhi Li; Yang-tai Guan (Molecular Neurobiology, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Retraction Note to: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Applying land use regression model to estimate spatial variation of PM2.5 in Beijing, China - Jiansheng Wu; Jiacheng Li; Jian Peng; Weifeng Li; Guang Xu; Chengcheng Dong (Environmental Science and Pollution Research, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Simulation of stable water isotopic composition in the atmosphere using an isotopic Atmospheric Water Balance Model - Xin‐Ping Zhang; Hua‐De Guan; Xin‐Zhu Zhang; Hua‐Wu Wu; Guang Li; Yi‐Min Huang (International Journal of Climatology, 2015)
In this article, we present a simplified isotopic Atmospheric Water Balance Model ( iAWBM ), to simulate spatial distribution and temporal variations of δ 18 O in atmospheric vapour and in precipitation, and the correlations of δ 18 O in precipitation with precipitation amount and with temperature. This method overcomes deficiencies of the Global Network of Isotopes in Precipitation ( GNIP ) due to its limitation in space and time resolution and those of the isotope‐enabled General Circulation Models ( iGCM s) due to its complexity. The simulated results reproduce well the latitude effect, continent effect and seasonality of δ 18 O in global precipitation. The simulation suggests that the precipitation amount effect occurs mainly in the low‐mid latitude oceans and monsoon areas, and the simulated temperature effect occurs mainly in the mid‐high latitude continents. However, the simulation results also indicate some temperature effect in some low‐latitude areas where the precipitation amount effect is strong. The modelled precipitation isotopic composition is compared to 3‐year observations in Changsha, China (2010–2012). The simulations reproduce the observed seasonal variations of δ 18 O in precipitation. The basic characteristics that stable isotopes in precipitation are depleted during the rainy season and enriched during the dry season, and the observed amount effect is well simulated under daily time scale. The simulated weighted average δ 18 O (−6.58‰) in precipitation during the prevailing winter monsoon season (October–March) is almost the same as the observed δ 18 O in the same period (−6.56‰), but the simulated δ 18 O (−9.58‰) during the prevailing summer monsoon season (April–September) is lower than the observed δ 18 O (−7.66‰). The simulation result also shows temporal variations of vapour isotopic composition in the atmosphere, and the proportional contributions from horizontal vapour exchange, precipitation and evaporation.

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Phytoextraction of uranium from contaminated soil by Macleaya cordata before and after application of EDDS and CA - Chang-wu Li; Nan Hu; De-xin Ding; Jin-song Hu; Guang-yue Li; Yong-dong Wang (Environmental Science and Pollution Research, 2015)

Late Permian–Triassic siliciclastic provenance, palaeogeography, and crustal growth of the Songpan terrane, eastern Tibetan Plateau: evidence from U–Pb ages, trace elements, and Hf isotopes of detrital zircons - Yu-Xiu Zhang; Lu Zeng; Zhi-Wu Li; Cheng-Shan Wang; Kai-Jun Zhang; Wen-Guang Yang; Tong-Lou Guo (International Geology Review, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

RETRACTED ARTICLE: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2014)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

Voltage stability in a long-distance power transmission system impacted by the geoelectric field due to a geomagnetic disturbance - Wei-li Wu; Lian-guang Liu; Chun-ming Liu (Earth Science Informatics, 2014)

Dioxin and Dioxin-Like Compounds Suppress Acetylcholinesterase Activity via Transcriptional Downregulations In Vitro - Hai-Ming Xu; Heidi Qunhui Xie; Wu-Qun Tao; Zhi-Guang Zhou; Shuai-Zhang Li; Bin Zhao (Journal of Molecular Neuroscience, 2014)

Molecular cloning and dimorphic expression of growth hormone (gh) in female and male spotted scat Scatophagus argus - Si-Ping Deng; Bo Wu; Chun-Hua Zhu; Guang-Li Li (Fisheries Science, 2014)

Awareness is essential for differential delay eyeblink conditioning with soft-tone but not loud-tone conditioned stimuli - He Huang; Bing Wu; Qiong Li; Juan Yao; Xuan Li; Yi Yang; Guang-Yan Wu; Jian-Feng Sui (Neuroscience Bulletin, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Curcumin induces apoptosis in human gastric carcinoma AGS cells and colon carcinoma HT-29 cells through mitochondrial dysfunction and endoplasmic reticulum stress - Aili Cao; Qi Li; Peihao Yin; Yang Dong; Hailian Shi; Li Wang; Guang Ji; Jianqun Xie; Dazheng Wu (Apoptosis, 2013)

Zircon U–Pb and pyrite Re–Os age constraints on pyrite mineralization in the Yinjiagou deposit, China - Ming-Tian Zhu; Lian-Chang Zhang; Guang Wu; Xin-Di Jin; Peng Xiang; Wen-Jun Li (International Geology Review, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

3,3-Dimethyl-1-butanol, a parakairomone component to Aleurodicus dispersus (Hemiptera: Aleyrodidae) - Li-Xia Zheng; Wei-Jian Wu; Guang-Wen Liang; Yue-Guan Fu (Arthropod-Plant Interactions, 2013)

A mutation in a coproporphyrinogen III oxidase gene confers growth inhibition, enhanced powdery mildew resistance and powdery mildew-induced cell death in Arabidopsis - Chuan-yu Guo; Guang-heng Wu; Jin Xing; Wen-qi Li; Ding-zhong Tang; Bai-ming Cui (Plant Cell Reports, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)

Effect of Fluoride on Insulin Level of Rats and Insulin Receptor Expression in the MC3T3-E1 Cells - Chun-yan Hu; Li-qun Ren; Xi-ning Li; Nan Wu; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2012)

Variations in soil culturable bacteria communities and biochemical characteristics in the Dongkemadi glacier forefield along a chronosequence - Guang-Xiu Liu; Ping Hu; Wei Zhang; Xiukun Wu; Xuan Yang; Tuo Chen; Manxiao Zhang; Shi-Weng Li (Folia Microbiologica, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Enhanced Anti-Diabetic Activity of a Combination of Chromium(III) Malate Complex and Propolis and its Acute Oral Toxicity Evaluation - Xiang-Yang Wu; Fang Li; Ting Zhao; Guang-Hua Mao; Jing Li; Hong-Yuan Qu; Yue-Na Ren; Liu-Qing Yang (Biological Trace Element Research, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Synthesis and crystal structure of chalcones as well as on cytotoxicity and antibacterial properties - Jianzhang Wu; Cong Wang; Yuepiao Cai; Jing Peng; Donglou Liang; Yunjie Zhao; Shulin Yang; Xiaokun Li; Xiaoping Wu; Guang Liang (Medicinal Chemistry Research, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Propagation of Gentiana macrophylla (Pall) from hairy root explants via indirect somatic embryogenesis and gentiopicroside content in obtained plants - Hai Jun Wu; Xin Xin Wang; Yan Li; Dong Guang Zhang; Bing Zhang; Xin Yu Wang (Acta Physiologiae Plantarum, 2011)

Methyl-1-hydroxy-2-naphthoate, a novel naphthol derivative, inhibits lipopolysaccharide-induced inflammatory response in macrophages via suppression of NF-κB, JNK and p38 MAPK pathways - Jun-Yan Zhang; Hong Jin; Guang-Fa Wang; Peng-Jiu Yu; Shao-Yu Wu; Zheng-Guang Zhu; Zhong-Huang Li; Yuan-Xin Tian; Wei Xu; Jia-Jie Zhang; Shu-Guang Wu (Inflammation Research, 2011)

Exogenous gibberellic acid increases the fruit weight of ‘Comte de Paris’ pineapple by enlarging flesh cells without negative effects on fruit quality - Yun-He Li; Yong-Jie Wu; Bei Wu; Ming-Hong Zou; Zhi Zhang; Guang-Ming Sun (Acta Physiologiae Plantarum, 2011)

A high-throughput method for screening of Aspergillus niger mutants with high transglycosylation activity by detecting non-fermentable reducing sugar - Gui-guang Chen; Wei Li; Yun-kai Zhang; Yong-ling Qin; Kong-yang Wu; Zhi-qun Liang (World Journal of Microbiology and Biotechnology, 2011)

Targets for human encoded microRNAs in HBV genes - Fang-li Wu; Wei-Bo Jin; Jia-hong Li; Ai-Guang Guo (Virus Genes, 2011)

Bacillus hunanensis sp. nov., a slightly halophilic bacterium isolated from non-saline forest soil - Yi-Guang Chen; Di-Fei Hao; Qi-Hui Chen; Yu-Qin Zhang; Jian-Ben Liu; Jian-Wu He; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Microarray analysis of the gene expression profile in the midgut of silkworm infected with cytoplasmic polyhedrosis virus - Ping Wu; Xiu Wang; Guang-xing Qin; Ting Liu; Yun-Feng Jiang; Mu-Wang Li; Xi-Jie Guo (Molecular Biology Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Yaniella soli sp. nov., a new actinobacterium isolated from non-saline forest soil in China - Yi-Guang Chen; Jun Chen; Qi-Hui Chen; Shu-Kun Tang; Yu-Qin Zhang; Jian-Wu He; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Berberine suppresses intestinal disaccharidases with beneficial metabolic effects in diabetic states, evidences from in vivo and in vitro study - Li Liu; Yun-Li Yu; Jian-Song Yang; Yang Li; Yao-Wu Liu; Yan Liang; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Isolation and characterization of polymorphic microsatellite markers in the yellow catfish, Pelteobagrus fulvidraco - Guang-Fu Hu; Hong-Wei Liang; Zhong Li; Chang-Zhong Wang; Qin-Chao Wu; Xiang-Jiang Liu; Xiang-Zhong Luo; Gui-Wei Zou (Conservation Genetics Resources, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Studies on optimization of nitrogen sources for astaxanthin production by Phaffia rhodozyma - Hui Ni; Qi-he Chen; Hui Ruan; Yuan-fan Yang; Li-jun Li; Guang-bin Wu; Yang Hu; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2007)

The expression of CD40-CD40L and activities of matrix metalloproteinases in atherosclerotic rats - Min Wu; Yu-Guang Li (Molecular and Cellular Biochemistry, 2006)

Mass culture of Undaria gametophyte clones and their use in sporeling culture - Chaoyuan Wu; Dapeng Li; Haihang Liu; Guang Peng; Jianxin Liu (Hydrobiologia, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)